Isolate and Characterization of Lactic Acid Bacteria (LAB) in Local Nira as Probiotic Starter Candidates - Aini Aini; Jumari Ustiawaty; Edy Kurniawan; Alfin Maulana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Probiotics are dietary supplements that contain lactic acid bacteria (BAL), which are capable of converting sugars (including lactose). Probiotics are used in the prevention of infectious diseases. Nira is often used as an ingredient to make alcoholic beverages (tuak) and sugar, but it has not been able to increase the economic value of sap water. The purpose of this study was to isolate lactic acid bacteria in sap as a probiotic candidate. The method in this study was carried out by isolating lactic acid bacteria in sap with a dilution series of 10-0, 10-1, 10-2, 10-3, 10-4, 10-5, and 10-6, then pipetting 1 ml into a cup petri dish and incubating in an anaerobic jar equipped with Anaerocult for 2 x 24 hours. Then macroscopic and microscopic observations were made and sugar and catalase tests were carried out to determine the type of bacteria found. The results of the isolation and characterization of bacteria in the sap were found to be 4 isolates, namely isolate 1A, which is Bacillus coagulans bacteria. Isolate 1B was a Bacillus licheniformis bacteria. Isolates 2A and 2B are bacteria from the genus Lactobacillussp.